Health Problems Burden Among Thai Hajj Pilgrims During Hajj Season 2015-2019: Updated Situation of COVID-19 - Chonjaroen, Hatairat; Vatcharavongvan, Pasitpon; Nomsiri, Apicha (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The Hajj pilgrimage to Mecca, Saudi Arabia, is one of the largest annual mass gatherings in the world, and has a strong impact on international public health. And including Thai pilgrims. Each year, Thai dispatches roughly 10,000 pilgrims to join the Hajj. It is very crowded with many health risks, that create health problems among the pilgrims in every Hajj season. This paper presents an overview from a systematic search of the published literature on health risks and services in the Hajj for 2015-2019, with the aim of providing health policy recommendations to prevent health risks. Of the 335 studies initially identified, 30 met the inclusion criteria for the review. Studies identified were diverse in methodology and focus. The results were classified into 5 main categories: communicable diseases, non-communicable diseases, mental health, injury and other problems and health services. Hajj has posed substantial health related problems to the pilgrims, possible public health threats to the indigenous population, between host and home countries, and also to the global health security. A good strategic public health plan for physical and mental health for the pilgrims prior to departure should be implemented. It is important to improve the health facilities and use well-trained medical personnel during Hajj. Health monitoring among pilgrims after home arrival should be done. These measures should be continuously done in order to minimize the risks and negative impacts.Although, improvement was observed throughout the years, there are always new public health challenges in each Hajj season. There is a need to improve health management of the Hajj, particularly by strengthening international collaboration.